Electroacupuncture therapy in inflammation regulation: current perspectives - Park JY; Namgung U (Dove Medical Press, 2018)
Ji-Yeun Park, Uk Namgung Department of Oriental Medicine, Daejeon University, Daejeon, South Korea Abstract: Although acupuncture therapy is increasingly used to treat diverse symptoms and disorders in humans, its underlying mechanism is not known well. Only recently have experimental studies begun to provide insights into how acupuncture stimulation generates and relates to pathophysiological responsiveness. Acupuncture intervention is frequently used to control pathologic symptoms in several visceral organs, and a growing number of studies using experimental animal models suggest that acupuncture stimulation may be involved in inducing anti-inflammatory responses. The vagus nerve, a principal parasympathetic nerve connecting neurons in the central nervous system to cardiovascular systems and a majority of visceral organs, is known to modulate neuroimmune communication and anti-inflammatory responses in target organs. Here, we review a broad range of experimental studies demonstrating anti-inflammatory effects of electroacupuncture in pathologic animal models of cardiovascular and visceral organs and also ischemic brains. Then, we provide recent progress on the role of autonomic nerve activity in anti-inflammation mediated by electroacupuncture. We also discuss a perspective on the role of sensory signals generated by acupuncture stimulation, which may induce a neural code unique to acupuncture in the central nervous system. Keywords: electroacupuncture, anti-inflammation, vagus nerve, animal model, acupuncture mechanism